Knowledge and Awareness Among Dental Students Regarding College Students and Eating Habits - Kajol Kumari Sah; K.V.N.R.Pratap; T.Madhavi padma; V.Srujan kumar; Surbhit singh; Santhapuri Nikhila Reddy (International Journal of Allied Medical Sciences and Clinical Research, 2025)
Over the past few decades, unhealthy eating behaviors have contributed to a rise in overweight and obesity among young adults. This study aimed to assess the knowledge and awareness among dental students regarding college students’ eating habits. A cross-sectional online survey was conducted among 204 dental students from Mamata Dental College, Khammam, using a 13-item self-administered questionnaire. Data were analyzed using SPSS version 29 and chi-square tests to compare awareness based on gender and year of study. Results showed that female students demonstrated higher awareness than males, while interns had the highest knowledge levels followed by second-, fourth-, third-, and first-year students. Statistically significant differences were observed for certain questions (p < 0.05). The findings suggest that although dental students possess basic knowledge of nutrition, greater emphasis on dietary education within the curriculum is needed to strengthen their ability to promote healthy eating and preventive oral healthcare.